2014
DOI: 10.1080/08959285.2014.956177
|View full text |Cite
|
Sign up to set email alerts
|

Do Employees Know How Their Supervisors View Them? A Study Examining Metaperceptions of Job Performance

Abstract: This study investigated employees' views about how their supervisors would rate their job performance (i.e., employees' metaperceptions). Two hundred forty employees from a high-tech firm provided self-and metaperception job performance ratings, and their supervisors also provided ratings of the employees' performance. The study produced several notable findings, including that metaperceptions were more strongly related to supervisory ratings than were self-ratings, that meta-accuracy was stronger for task ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…At work, competence is a valued individual characteristic, which may explain why meta-perceptions of expertise have important implications for employee motivation and performance (e.g., Grutterink et al, 2013). In this line of research, studies explore how employees believe their leaders evaluate their competence, and how that relates to their performance (e.g., technical competence: Tan & Jamal, 2006; task and contextual performance: Hu et al, 2014). For example, Qu et al (2015) found that employees' beliefs of how their supervisors assess their creativity (leader creativity expectations) can improve their actual creativity.…”
Section: Competencementioning
confidence: 99%
See 2 more Smart Citations
“…At work, competence is a valued individual characteristic, which may explain why meta-perceptions of expertise have important implications for employee motivation and performance (e.g., Grutterink et al, 2013). In this line of research, studies explore how employees believe their leaders evaluate their competence, and how that relates to their performance (e.g., technical competence: Tan & Jamal, 2006; task and contextual performance: Hu et al, 2014). For example, Qu et al (2015) found that employees' beliefs of how their supervisors assess their creativity (leader creativity expectations) can improve their actual creativity.…”
Section: Competencementioning
confidence: 99%
“…For example, reflected self-efficacy (a form of meta-perception regarding how others assess their ability to perform) predicted creative performance over and above self-rated self-efficacy (Litrico & Choi, 2013). Additionally, the more employees believe that their organization, supervisors, and peers recognize and affirm their individual value, competence, expertise, and abilities in relation to their individual or team tasks, the better they perform (e.g., perceived expertise affirmation: Grutterink et al, 2013; meta-perceptions of job performance: Hu et al, 2014). This corresponds to research that suggests that people continuously strive for affirmation of positive aspects of their identity at work (e.g., Ashforth et al, 2017) because of their fundamental need to feel valued by others they deem important.…”
Section: Competencementioning
confidence: 99%
See 1 more Smart Citation
“…These include the need for control and the need to maintain positive self-views (i.e., for self-enhancement and self-protection). Work outcomes, work roles, task assignments, recognition, and the feedback received in the course of the work process provide individuals with information about their current level of success (Hu, Kaplan, Wei, & Vega, 2014), which can be more or less congruent with self-concept-generated expectations. To restore self-concept congruity (i.e., control), individuals need to engage in self-regulatory activities, such as trying to shape the environment, or reinterpreting unexpected outcomes to preserve consistent self-perceptions across time (exerting secondary control; cf.…”
Section: A Self-regulation Account Of the Job Performance-job Satisfamentioning
confidence: 99%
“…Concerning other social outcomes, the literature is scarce. However, we know that meta-accuracy is influenced by the need to convey a specific impression to others or a high need for approval (Albright & Malloy, 1999;Ashford, Blatt, & Vandewalle, 2003;Hu, Kaplan, Wei, & Vega, 2014). In return, successful attempts to convey said impressions 6 depends on their metaperception (Schlenker & Weigold, 1992).…”
Section: Outcomes Of Meta-accuracymentioning
confidence: 99%